A taxonomic revision of the genus Haplosyllis Langerhans, 1887 (Polychaeta: Syllidae: Syllinae) - Lattig, Patricia; Martin, Daniel (Zootaxa, 2009)
The genus Haplosyllis Langerhans, 1887 is revised based on available types and newly collected specimens. 19 species are considered as valid, five as incertae sedis and four are referred to nomina dubia. Trypanoseta (Imajima, 1966) is synonymised with Haplosyllis, as the presence of trepan is considered a non-robust taxonomic feature, affecting H. ohma new comb. (Imajima & Hartman, 1964) and H. granulosa new comb. (Lattig, San Martín & Martín, 2007). Haplosyllis streptocephala (Grube, 1857) is a new combination and two species are considered to belong to Alcyonosyllis Glasby & Watson, 2001: A. bisetosa new comb. (Hartmann-Schröder, 1960) and A. gorgoniacola new comb. (Sun & Yang, 2004). All valid species are described and figured except those described during the last decade, which only includes diagnoses and chaetae illustrations. A dichotomous key to all valid species of Haplosyllis is provided.